Highway traffic flow equation depending on DTCA - AlGhamdi, A.; Eren, Halit (2012)
This paper discusses Dynamic Traffic Cellular Automata (DTCA) model. It integrates acceleration, deceleration, and reaction probability functions. The effects of these probability functions on the traffic flow has been explained and shown that they have a major impact on the prediction of traffic flow. This mathematical approach has been verified by simulations.